UPAYA PENCEGAHAN PENULARAN COVID-19 PADA MASYARAKAT KAMPUANG SUMUA KELURAHAN LADANG CAKIAH KOTA BUKITTINGGI - Anggela Pradiva Putri; Mega Utami Basra; Melisa Yenti; Devhani Fitri; Intan Rahma Sari; Ulfa Fadhila Farhan (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
Coronavirus Disease 2019 (Covid-19) is a new type of disease that humans have never previously identified. In Indonesia, every time there is an increase in cases of the impact of Covid-19. In fact, the spread of this virus has reached various areas, including West Sumatra (West Sumatra). In West Sumatra, the area with the highest cases in Padang City. The high number of cases of this virus's spread has resulted in the government implementing PSBB (Large-Scale Social Restrictions) regulations at the provincial level. For Bukittinggi, most people have jobs with daily wages, such as traders, public transport drivers, motorcycle taxi drivers, farmers, and others. The community complained about the impact of this PSBB, which resulted in the loss of their income for their daily needs. The purpose of this activity is to improve the community's food security through the distribution of necessities, increase public knowledge through leaflet media, and the provision of non-medical masks as an effort to prevent Covid-19 transmission. This activity was carried out in RT 04 Sumua Village, Ladang Cakiah Village, Aur Birugo Tigo Baleh District, Bukittinggi City. The activity method is counseling and giving leaflets, masks, and raw food packages. The results of activities carried out are in the form of counseling about Covid-19 to the people of Kampung Sumua in the form of leaflets distributed to the community directly to each house to avoid gatherings. Subsequently, masks were given as a form of prevention of Covid-19. The next effort was to provide direct assistance, namely distributing food packages to Sumua Village people, which were affected by the PSBB during the Covid-19 period in rice, eggs, cooking oil, and sugar, many as 40 packages. This activity can have a positive impact on the community by providing material assistance. The hope is that people can avoid Covid-19 and the spread of this virus in the future, and our lives can take place naturally.